The responses of lecturers on online learning in pandemic covid-19 - Harahap, Nurhanna; Rusli, Muhammad; ., Jupriaman (KnE Social Sciences, 2023)
Government of Indonesia ordered every educational institution to do online learning to break the chain of Corona virus disease. Because of that, Teacher Training and Education Faculty (FKIP) of UNIVA Labuhanbatu did teaching learning process by online learning system. This condition made the lecturers gave different responses. So, this research aims to reveal the responses of lecturers on doing online learning in covid-19 pandemic. The data were collected through questionnaires. The data revealed that there were different responses of lecturers of FKIP of UNIVA Labuhanbatu.The mean obtained was 63.73%. Based on the mean, it can be conclude that the responses of the lecturers of FKIP UNIVA Labuhanbatu were categorized with agree with doing online learning in pandemic Covid-19. Keywords: Online learning; covid-19; lecturers